Arte dos vegetais - Paiva, Aline Gonçalves; Silva, Bruna de Lima; Bernhard , Cristiane Otília Colossi; Santos , Eliana Ferreira dos; Borges, Fabiana Souza; Oliveira , Queille Priscila Sales de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf